Case report: Is mid-trimester cesarean section an unrecognized risk factor for accidental extension to the lower uterine segment? Predstavitev primera: Je carski rez v drugem trimestru nosečnosti nerazpoznavni dejavnik tveganja za nenamerno podaljšanje histerotomije v spodnji del maternice? - Al Mahdawi, Leyla; Kuder, Lucija; Mujezinović, Faris (Acta Medico-Biotechnica, 2021)
Purpose: Hysterotomy extension at the time of cesarean section is frequent and associated with severe blood loss, risk of transfusion, and unplanned hysterectomy. Cesarean section during the second stage of labor is the most important riskfactor.Case report: We describe a case of a 35-year-old gravida 4 para 1 at 26+1 weeks gestation who underwent a repeat cesarean section. An unintentional hysterotomy extension led to severe blood loss. The patient was discharged on day 4 after the operation in stable condition.Conclusion: Hysterotomy extension is associated with higher maternal morbidity and mortality. Blunt expansion of the hysterotomy and a reverse breech extraction are associated with a lower uterine tear rate.
Keywords: second trimester cesarean section; unintentional hysterotomy tear; cesarean section technique